A NIR-remote controlled upconverting nanoparticle: an improved tool for living cell dye-labeling. (1st October 2015) - Zheng, Bin; Gong, Xiaoqun; Wang, Hanjie; Wang, Sheng; Wang, Huiquan; Li, Wei; Tan, Jian; Chang, Jin
Abstract: In living cells, due to the selective permeability and complicated cellular environment, the uptake efficiency and fluorescence decay of organic dyes during dye-labeling may be influenced, which may eventually result in poor fluorescent imaging. In this work, a protocol of UCNs@mSiO2 -(FA and Azo) core–shell nanocarriers was designed and prepared successfully. The core–shell nanocarriers were assembled from two parts, including a mesoporous silica shell surface modified by folate (FA) and azobenzene (Azo), and an upconverting nanocrystal (UCN) core. The mesoporous silica shell is used for loading organic dyes and conjugating folate which helps to enhance the cellular uptake of nanocarriers. The UCN core works as a transducer to convert near infrared (NIR) light to local UV and visible light to activate a back-and-forth wagging motion of azobenzene molecules on the surface, while the azobenzene acts as a molecular impeller for propelling the release of organic dyes. The nanocarriers of loading organic dyes can maintain the stability of the fluorescent imaging effect better than free organic dyes. The experimental results show that with the help of the nanoparticle, cell uptake efficiency of the model dyes of rhodamine and 4′, 6-diamidino-2-phenylindole (DAPI) was significantly improved. The release of dyes can only be triggered by NIR light exposure and their quantity is highly dependent on the duration of NIR light exposure, thus realizing NIR-regulated dye release spatiotemporally. Our work may open a novel avenue for precisely controlling UCN-based living cell imaging in biotechnology and diagnostics, as well as studying cell dynamics, cell–cell interactions, and tissue morphogenesis.